2023
DOI: 10.3390/jcm12041322
|View full text |Cite
|
Sign up to set email alerts
|

Combining Neuropsychological Assessment with Neuroimaging to Distinguish Early-Stage Alzheimer’s Disease from Frontotemporal Lobar Degeneration in Non-Western Tonal Native Language-Speaking Individuals Living in Taiwan: A Case Series

Abstract: Neuropsychological tests (NPTs), which are routinely used in clinical practice for assessment of dementia, are also considered to be essential for differential diagnosis of Alzheimer’s disease (AD) and frontotemporal lobar degeneration (FTLD), especially the behavioral variants of frontotemporal dementia (bvFTD) and primary progressive aphasia (PPA) at their initial clinical presentations. However, the heterogeneous features of these diseases, which have many overlapping signs, make differentiation between AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have also shown a strong interest in integrating features from different neuroimaging modalities to predict neuropsychological assessments based on machine learning techniques ( Bhagwat et al, 2019 ; Tabarestani et al, 2020 ; Hojjati and Babajani-Feremi, 2022 ). Some studies have combined neuropsychological scores with neuroimaging biomarkers to find the progression trend or predict neuropsychological assessments ( Gill et al, 2020 ; Tabarestani et al, 2020 ; Kuo et al, 2023 ). However, the use of several predictors in such studies can result in the inclusion of unrelated information in their different prediction tasks, leading to a decrease in regression performance ( Zhou et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown a strong interest in integrating features from different neuroimaging modalities to predict neuropsychological assessments based on machine learning techniques ( Bhagwat et al, 2019 ; Tabarestani et al, 2020 ; Hojjati and Babajani-Feremi, 2022 ). Some studies have combined neuropsychological scores with neuroimaging biomarkers to find the progression trend or predict neuropsychological assessments ( Gill et al, 2020 ; Tabarestani et al, 2020 ; Kuo et al, 2023 ). However, the use of several predictors in such studies can result in the inclusion of unrelated information in their different prediction tasks, leading to a decrease in regression performance ( Zhou et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…PET scans utilizing florbetapir, flutemetamol, or florbetaben may confirm AD [23]. Chin-Yun Kuo et al (2023) [24] discussed the significance of integrating neuropsychological assessment with neuroimaging in order to identify AD in its initial stages. Researchers can obtain valuable information on brain anatomical components from high-resolution MRI images.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown a strong interest in integrating features from different neuroimaging modalities to predict neuropsychological assessments based on machine learning techniques [15,34]. Some studies have combined neuropsychological scores with neuroimaging biomarkers to find the progression trend or predict neuropsychological assessments [15,35,36]. However, the use of numerous predictors in such studies can lead to the inclusion of unrelated information in their different prediction tasks, leading to a decrease in regression performance [37].…”
Section: Introductionmentioning
confidence: 99%